-10(1x-2)+14=4x+160

Simple and best practice solution for -10(1x-2)+14=4x+160 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(1x-2)+14=4x+160 equation:


Simplifying
-10(1x + -2) + 14 = 4x + 160

Reorder the terms:
-10(-2 + 1x) + 14 = 4x + 160
(-2 * -10 + 1x * -10) + 14 = 4x + 160
(20 + -10x) + 14 = 4x + 160

Reorder the terms:
20 + 14 + -10x = 4x + 160

Combine like terms: 20 + 14 = 34
34 + -10x = 4x + 160

Reorder the terms:
34 + -10x = 160 + 4x

Solving
34 + -10x = 160 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
34 + -10x + -4x = 160 + 4x + -4x

Combine like terms: -10x + -4x = -14x
34 + -14x = 160 + 4x + -4x

Combine like terms: 4x + -4x = 0
34 + -14x = 160 + 0
34 + -14x = 160

Add '-34' to each side of the equation.
34 + -34 + -14x = 160 + -34

Combine like terms: 34 + -34 = 0
0 + -14x = 160 + -34
-14x = 160 + -34

Combine like terms: 160 + -34 = 126
-14x = 126

Divide each side by '-14'.
x = -9

Simplifying
x = -9

See similar equations:

| 7(x-3)=-42 | | 3(5-2x)-(8-6x)=-9+2(3x+4)-10 | | 6x-4=30 | | 9.2=4.4s-4 | | -2(5s-2)-4=-3(8s+0)-3 | | 3(5x+8)-2(x-6)= | | -22=-5x+13 | | Y=3(5-x) | | (x+2)=1.3*x | | [[4v-3]]=[[6v-15]] | | 4x+(-28)=0 | | 15=3(1x-3) | | (-.75)(-2x)(1.33)(0.2y)(0)= | | s-5t=-5 | | -10x+12=5x+132 | | (.5)(4x)(-2)(7y)(01)= | | 16x^3y^3+32x^2y^4+15xy^5= | | x+3=4x-8 | | -x-3=x+25 | | 2x-6-8x-7= | | 13x+11=8x+11 | | -2x+117=7x | | 7x^2-7x-6=0 | | 7(3s+10)=91 | | 3x+12=-5x+52 | | x*x+4x-3=0 | | 7(2l+8)=112 | | -15x-40=5x | | x-x=100 | | y=550+40x | | -15=-3(1x+8) | | 24h+-35=853 |

Equations solver categories